2012
DOI: 10.2147/vhrm.s33194
|View full text |Cite
|
Sign up to set email alerts
|

Glimepiride: evidence-based facts, trends, and observations

Abstract: Type 2 diabetes mellitus is characterized by insulin resistance and progressive β cell failure; therefore, β cell secretagogues are useful for achieving sufficient glycemic control. Glimepiride is a second-generation sulfonylurea that stimulates pancreatic β cells to release insulin. Additionally, is has been shown to work via several extra pancreatic mechanisms. It is administered as monotherapy in patients with type 2 diabetes mellitus in whom glycemic control is not achieved by dietary and lifestyle modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
54
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 40 publications
2
54
1
2
Order By: Relevance
“…In non-diabetics with normal HbA 1c levels, acupuncture treatments caused no change in the levels, as acupuncture is not expected to cause a deviation from normal physiologic status. HbA 1c levels in our diabetic patients fell a similar amount (but fell more quickly) as those of diabetic patients on medical therapy in previous studies [29,30]. The relatively rapid decrease in HbA 1c in our patients was greater than the drug-only or diet effect noted in other studies [14,[30][31][32][33].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In non-diabetics with normal HbA 1c levels, acupuncture treatments caused no change in the levels, as acupuncture is not expected to cause a deviation from normal physiologic status. HbA 1c levels in our diabetic patients fell a similar amount (but fell more quickly) as those of diabetic patients on medical therapy in previous studies [29,30]. The relatively rapid decrease in HbA 1c in our patients was greater than the drug-only or diet effect noted in other studies [14,[30][31][32][33].…”
Section: Discussionsupporting
confidence: 73%
“…In our study, HbA 1c levels fell a mean of 0.6% (max 1.3%) in obese diabetics after only 10-12 weeks of acupuncture treatment. However, vildagliptin or glimepiride did not induce as much weight loss as acupuncture treatment did in our diabetic patients [29,30]. In the literature, there are a few studies regarding the effects of acupuncture on HbA 1c levels.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In calculating the sulfonylurea dose, we considered 1 mg glimepiride to be equivalent to 40 mg gliclazide or 1.25 mg glibenclamide, as previously reported 14,15 . We calculated propensity scores for the likelihood of discontinuing or maintaining sulfonylurea at the lowest dose as add-on to ipragliflozin using baseline covariates in a multivariate logistic regression model.…”
Section: Discussionmentioning
confidence: 99%
“…19,25 Glimepiride on the other hand has favourable pleiotropic cardiovascular effects, low incidence of hypoglycaemia and is the preferred sulfonylurea in obese patients. [26][27][28] Analysing FPG and HbA1C values, pre-treatment and 1 year post treatment of 5 commonly prescribed treatment groups showed that all treatment regimens showed significant reduction in FPG except metformin monotherapy. Fasting plasma glucose is a highly unreliable value for assessing glycemic control since it is dependent on previous day's diet, medication and exercise.…”
Section: Discussionmentioning
confidence: 99%